Crystallization of NaHCO3 for concomitant CO2 sequestration and enrichment of lithium cations concentration in high salinity brines - María L Vera; Cecilia N Pereyra; César H Díaz Nieto; Victoria Flexer (Sustainability Science and Technology)
Continental brines, with total dissolved solids ranging from 170–350 g l ^−1 , are the most abundant lithium resources, although lithium is one of the minor brine components, at concentrations around 1%. Amongst several requirements, for an efficient lithium recovery, it is imperative to improve the Li ^+ to Na ^+ concentration ratio. Here we report a membrane electrolysis process for Na ^+ abatement from brines avoiding solid incrustations inside the reactor and minimizing lithium losses. Sodium is precipitated by CO _2 absorption and conversion to bicarbonate anions under basic conditions. Variables such as CO _2 flow rate and applied current densities were modified under different experimental designs. Three different arrangements were tested, with the best results found for an uncoupled CO _2 conversion and the recovery of the effluent from solid washing. Following this strategy, a reduction in the Na ^+ content of approximately 70% was achieved with a decrease of more than 3-fold in the Na ^+ /Li ^+ ratio of concentrations. Lithium recoveries of up to 66.6% in the catholyte were obtained with a mass balance close to 100% for both lithium and sodium. The proposed methodology has the potential to capture about 146.4 g of CO _2 per liter of electrolyzed brine, permanently storing CO _2 as mineral carbonates.